Clinical Attributes of Tiletamine-Zolazepam Induced Anesthesia with and without Xylazine Premedication in Dogs - Koli, Pooja H.; Parikh, Pinesh V.; Mahla, Jalendra K.; Barot, Hiren M. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Two anesthetic protocols were evaluated in 20 dogs (12 Female and 8 Male) of different breeds presented for surgical interventions to study anesthetic efficacy as well as to assess physiological and haemato-biochemical alterations following tiletamine-zolazepam (TZ) combination as induction agent with and without xylazine premedication, and maintenance on isoflurane. The dogs were randomly allotted to two groups consisting of ten patients in each. Atropine (0.04 mg/kg, IM) was common in both groups, and Group I patients also received xylazine (0.5 mg/kg, IM). Induction was achieved by tiletamine-zolazepam @ 3 mg/kg, IV and maintained on isoflurane. The induction time was significantly shorter in Group I where patients were premedicated with xylazine as compared to Group II. An after-effect of TZ induction was transient post-induction apnoea in 11 patients. Baseline physiological parameters (pulse rate, respiratory rate, SpO2, and rectal temperature) were determined. The changes in physiological parameters during maintenance remained within biologically acceptable limits. Among haemato-biochemical parameters, a non-significant decrease was observed in Hb, PCV, TLC, TEC, TP, AST, ALT, creatinine, and BUN during anesthesia and after recovery. The anesthetic duration and complete recovery time were longer in Group I compared to Group II. The study confirms induction of balanced anesthesia using atropine, xylazine, tiletamine-zolazepam combinations, and isoflurane maintenance with efficient nociception during surgical procedures.